Therapeutic plasma exchange accelerates immune cell recovery in severe COVID-19 - Aurelie Guironnet-Paquet; Aurelie Guironnet-Paquet; Hind Hamzeh-Cognasse; Frederic Berard; Fabrice Cognasse; Fabrice Cognasse; Jean Christophe Richard; Hodane Yonis; Mehdi Mezidi; Olivier Desebbe; Bertrand Delannoy; Sophie Demeret; et al. (Frontiers in Immunology)
BackgroundImmunological disturbances (anti-type I IFN auto-antibody production, cytokine storm, lymphopenia, T-cell hyperactivation and exhaustion) are responsible for disease exacerbation during severe COVID-19 infections.MethodsIn this study, we set up a prospective, randomised clinical trial (ClinicalTrials.gov ID: NCT04751643) and performed therapeutic plasma exchange (TPE) in severe COVID-19 patients in order to decrease excess cytokines and auto-antibodies and to assess whether adding TPE to the standard treatment (ST, including corticosteroids plus high-flow rate oxygen) could help restore immune parameters and limit the progression of acute respiratory distress syndrome (ARDS).ResultsAs expected, performing TPE decreased the amount of anti-type I IFN auto-antibodies and improved the elimination or limited the production of certain inflammatory mediators (IL-18, IL-7, CCL2, CCL3, etc.) circulating in the blood of COVID-19 patients, compared to ST controls. Interestingly, while TPE did not influence changes in ARDS parameters throughout the protocol, it proved more effective than ST in reversing lymphopenia, preventing T-cell hyperactivation and reducing T-cell exhaustion, notably in a fraction of TPE patients who had an early favourable respiratory outcome. TPE also restored appropriate numbers of CD4+ and CD8+ T–cell memory populations and increased the number of circulating virus-specific T cells in these patients.ConclusionOur results therefore indicate that the addition of TPE sessions to the standard treatment accelerates immune cell recovery and contributes to the development of appropriate antiviral T-cell responses in some patients with severe COVID-19 disease.